Hubungan waktu tidur dengan kelebihan berat badan pada mahasiswa dan staf pengajar FK UISU - Novziransyah, Nanda; Daulay, Mutya Sarah (UNIVERSITAS SAM RATULANGI, 2018)
Being overweight is defined as an abnormal accumulation of body fat compared to normal body size. Its prevalence is increasing rapidly in a number of industrialized countries around the world and is becoming a pandemic that needs immediate attention. The cause is more complex than the simple paradigm of energy imbalance, but various mechanisms play a role in it, including sleep duration. The purpose of this study was to determine the relationship of sleep duration with overweight in student and lecturer in Medical Faculty of Islamic University of North Sumatera.This is an analytical research with cross sectional study design with stratified random sampling method; the samples were taken from each level proportionally, 100 samples, where the minimum sample is 77 samples.Data was analysed by using Spearman Correlation test. Based on the result of statistical test, the significance value of the relationship between sleep time and overweight at student of class of 2014 is p=0,556 (p>0,05), it can be concluded that there is no relation of sleep duration with overweight in students of FK UISU class of 2014. The significance value in the Students class of 2015 is p=0,928 (p>0,05), it can be concluded that there is no relation of sleep duration with overweight among them. The significance value in student of class of 2016 is p=0,518 (P> 0,05), which also be concluded as no relationship between sleep time and overweight among the sudents. And the lecturer value of significance p = 0,569 (p> 0,05) so it can be concluded that there is no relationship of sleep duration with overweight in Medical Faculty of Islamic University of North Sumatera.